Fabrication of nitrogen-rich graphitic carbon nitride/Cu2O (g-C3N4@Cu2O) composite and its enhanced photocatalytic activity for organic pollutants degradation - Muthukumaran, M. (Springer, 2020)
The present study deals with the synthesis, characterization, and testing of photocatalytic activity towards the degradation of organic dyes and for that, nitrogen-rich graphitic carbon nitride/cuprous oxide (g-C3N4@Cu2O) composite was synthesized with improved photocatalytic performance using the hydrothermal method. For the characterization of composite, many different techniques are employed such as Fourier transform infrared spectroscopy for the chemical functionality and bonding, diffused reflectance ultraviolet-visible spectroscopy for the optical properties, powdered X-ray diffraction patterning for the phase purity and crystal orientations, field emission scanning electron microscopy for the surface morphology, thermogravimetric analysis for the thermal stability, and dynamic light scattering spectroscopy for the zeta-potentials. On testing, we observed significant effects of photocatalytic activity in terms of the degradation of various dyes like methylene blue, rhodium-B, thymol blue, and blue ink solution under the UV light irradiation using 8 W xenon lamp. Such a significant activity of the composite can be linked to the increased light absorption, charge separation efficiency, and specific surface area as indicated by the UV-vis DRS analysis. Further, the mechanistic analysis confirmed the active role played by the holes (h(+)) and superoxide radicals (center dot O-2(-)) for photocatalytic dye degradation.